Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2006
DOI: 10.1590/s0103-166x2006000200004
|View full text |Cite
|
Sign up to set email alerts
|

Crianças com dificuldade de aprendizagem e a escola: emoções e saúde em foco

Abstract: Relações entre emoções e saúde de alunos com e sem dificuldade de aprendizagem foram analisadas por indicadores de ansiedade, depressão, stress, doenças físicas, queixas somáticas, faltas escolares, peso e altura. Responderam ao Inventário de Ansiedade Traço-Estado para Criança e à Escala de Stress Infantil 60 alunos (8-14 anos) da 3ª e 4ª série, divididos em G1 (desempenho inferior no Teste de Desempenho Escolar) e G2 (desempenho superior no Teste de Desempenho Escolar). A Escala de Sintomatologia Depressiva … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0
11

Year Published

2007
2007
2016
2016

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 9 publications
(14 reference statements)
2
5
0
11
Order By: Relevance
“…Given the obtained results in this study in which there were no statistically significant differences in the stress level among children with and without SLD, nor between boys and girls, these results were also observed in previous studies 12,13,17 .…”
Section: Discussionsupporting
confidence: 90%
See 3 more Smart Citations
“…Given the obtained results in this study in which there were no statistically significant differences in the stress level among children with and without SLD, nor between boys and girls, these results were also observed in previous studies 12,13,17 .…”
Section: Discussionsupporting
confidence: 90%
“…On the other hand, other studies have not found this association 12,13 , since there were no statistically significant differences in childhood stress indicators between the groups with and without learning disorders.…”
Section: Introductionmentioning
confidence: 66%
See 2 more Smart Citations
“…Para a seleção da amostra, 144 alunos dessa escola, que cursaram, em 2001, a segunda e terceira série, realizaram um teste de desempenho escolar (TDE) - (Stein, 1994) no final de 2001, como parte das atividades de um projeto integrado de pesquisa (Dias, Enumo & Azevedo Júnior, 2004;Dias, Enumo, Turini & Ferrão, 2003;Dias, Silva, Enumo & Rabbi, 2005). O TDE é um teste brasileiro composto por três subtestes: leitura, escrita e aritmética, que tem sido utilizado em pesquisas (Enumo, Ferrão & Ribeiro, 2006;Medeiros, Loureiro, Linhares & Marturano, 2000;Santa Maria & Linhares, 1999). A classificação do TDE tem três níveis: inferior, médio e superior, e é obtida por uma tabela correspondente a cada série.…”
Section: Método Participantesunclassified